Transformation analysis of the horizontal stability for geodetic points - Sütti Juraj (Acta Montanistica Slovaca, 2001)
Application of transformation methods is a useful means in deformation investigation. Philosophy of the transformation investigation of geodetic network point stability is based on applying appropriate transformation tools for this goal. Its procedure realisation and interpretation can be described by following item :- by measuring the geodetic networks and processing the results (adjustment) in the epoch t, there is defined the network realisation S and it can be obtained point coordinates C,- by the same processes in the epoch t´, there will be defined another network realisation S´ with point coordinated C´calculated,- coordinates C´ have to be changed using a convenient transformation model to coordinates Ct, that will be valid for epoch t.From the non identical coordinates C and Ct, there is computed the coordinate discrepancies dC = Ct C at the netpoints, that are generated by measuring errors, blunders of measurements and models and by the point horizontal movements. If the first two causes can be eliminated by suitable ways, the dc values can be held for indicators of horizontal point displacements only. Using approprial statistical tests, one may identifies points with statistical significant movements during the time t´ - t.There are presented two transformations using translation and rigid body model of point displacements.The testing procedures was applied for the horizontal geodetic network in the area of the Nuclear Power Plant in Jaslovské Bohunice. Dislocation of the point movements derived from: measuring, translation model, rigid body model with the corresponding dh contour lines are shown in the Fig. 1, 2, 3 and their values in the Tab. 1, 2. It can be seen, the dh values as regard their lengths and orientations are considerable similar. But this can´t exlude the fact, that from the theoretical point of view, the transformed dh are the more exact values for evaluation of the point displacements.